Potential of Cellulose Acetat Separator of Empty Palm Oil Fruit Bunches and Polyvinylidene Fluoride for Energy Storage Applications - Ginting, Delovita; Na Duma, Tulus; Rahmadani, Nofia; Suryani, Yola; Haryanti, Rismadani (POSITRON, 2023)
One of the components that play an important role in maintaining battery security is the separator. The separator plays a role in preventing short circuits due to direct exchange between the anode and cathode in the battery cell. To avoid leakage or short circuit during the process, the separator must have good mechanical properties. For this reason, modifications are needed to improve the characteristics of the separator. The modification process was carried out by mixing Poyvinylidene Fluoride (PVDF) and cellulose acetate (CA) polymers. The CA used in this study was obtained by utilizing natural waste extracts in the form of empty oil palm fruit bunches (EFB). This study aims to see the effect of variations in the addition of CA EFB and PVDF on the characteristics of the resulting separator. Synthesized CA EFB was characterized using Fourier Transfor Infrared (FTIR) spectroscopy which showed that cellulose had been successfully synthesized into cellulose acetate.. The separator produced in this study showed good electrolyte absorption, indicated by the occurrence of an oxidation-reduction reaction process on the hysteresis curve with a wider and reversible loop upon the addition of 0.2 g CA. The mechanical characteristics of the separator also increased with the addition of CA concentration, the separator with the addition of 0.3 g CA showed the highest tensile strength value of 62.335 MPa and the highest porosity value of 89.35%. The separator with the addition of 0.3 g of cellulose acetate also decomposes more quickly, indicated by a weight loss percentage of 60%. The results of this test indicate that the addition of CA EFB and PVDF can affect the physical and mechanical characteristics of the separator which has the potential to become a battery separator.